The Relationship between Physical Activity, Dietary Patterns, Sex, Age, and BMI of Employees of Dispora NTT - Yohanes Vianei Belo Boli; Honey Ivone Ndoen; Sarci Magdalena Toy (Universitas Nusa Cendana, 2021)
Working as an employee at the Department of Youth and Sports (Dispora), NTT province is likely to increase the risk of sedentary activities. A sedentary lifestyle can contribute to obesity. This study analyzed the relationship between physical activity, dietary patterns, sex, age, and the body mass index (BMI) of the Dispora employees in Indonesia's East Nusa Tenggara Province. The study used a cross-sectional study design. The chosen sample consisted of 60 Department of Youth and Sports employees, selected using a simple random sampling technique. This research directly assessed each participant's BMI, while all other data collated from questionnaires, including IPAQ, food recall (2 x 24 hours), and FFQ. In total, 51.6% of employees reported less physical activities, high dietary intake (45.0%), good consumption of foods (45.0%), high variety of foods (51.7%), were not at high risk of age (51.7%), and obese (55.0%). The results of the statistical analysis tests using chi-square and fisher's exact tests concluded that physical activity (p-value = 0.000) and energy intake (p-value = 0.000) had significant effects on BMI, while frequency of eating (p-value = 0.174), the variety of food consumed (p-value = 0.104), sex (p-value = 0.299), and age (p-value = 0.775) had no effect on BMI. Employees should maintain a normal BMI, sufficient physical activity, balanced nutrition, and regular check-ups.